Management of fever and acute painful crises in children with sickle cell disease in emergency departments: a tertiary hospital experience - Almahmoud, Tameem; Alnashwan, Tasneem; Al Kuhaimi, Lara; Essa, Mohammed F.; Al Balawi, Nouf; Jamaan, Khaled Al; Al-Harthy, Nesrin (Frontiers in Pediatrics, 2023)
Sickle Cell Disease (SCD) is highly prevalent in Saudi Arabia with variable demographics and access to health care facilities including emergency departments. Literature reviews for locally published articles are deficient in the in-depth evaluation of current emergency practices in managing patients with SCD. The study aims to assess the current emergency practice in managing SCD patients in tertiary hospitals. We reviewed data of 212 visits by patients with SCD over three years and assessed the current emergency department practices in managing common SCD crises, such as vaso-occlusive (VOC) and febrile episodes. Our findings revealed that 47.2%, 37.7 %, and 15% of the patients presented with pain, fever, or both, respectively. The patients were triaged level III according to the Canadian triage and acuity scale system in 89 % of the visits. The Median time for patients to see healthcare providers was 22 min. In the first 2 h, 86 % of the patients received at least one fluid bolus and 79% of them received appropriate analgesia for pain crises. Approximately 41.5 % of the patients with fever were admitted and received ceftriaxone as single intravenous antimicrobial agent. However, none of the patients had bacteremia. Only 2.4 % of the patients had either urinary tract infection or osteomyelitis based on imaging. ED management is a key factor in the successful management of patients with SCD in a timely manner by providing fluids, analgesia, and antibiotics. Adopting evidence-based guidelines and avoiding unnecessary admissions are suggested in clinically well patients with fever in the era of completed vaccination, antibiotic prophylaxis, and good access to care for patients with a clear viral infection focus.